Profile of adults users of smartphone applications for monitoring the level of physical activity and associated factors: A cross-sectional study - Vieira, Wesley de Oliveira; Ostolin, Thatiane Lopes Valentim di Paschoale; Simões, Maria do Socorro Morais Pereira; Proença, Neli Leite; Dourado, Victor Zuniga (Frontiers in Public Health, 2022)
Background: Smartphone applications (APPs) that monitor physical activity level (PAL) have the potential to bring health benefits. Although the profile of users is known in developed countries, this information is scarce in developing countries such as Brazil. Objectives: To characterize the profile of APP users to monitor PAL and assess the demographic, socioeconomic, clinical, physiological, and functional characteristics associated with the use of smartphone APPs to monitor physical activity in Brazilian adults. Methods: We assessed 176 asymptomatic men and 178 women (43 ± 12 years; 27 ± 5 kg/m2). In a cross-sectional design, we aasked participants about their current use of a smartphone APP containing PAL monitoring functionality, such as exercise session logs and/or step counts,. Also we evaluated schooling, socioeconomic status, classic self-reported cardiovascular risk factor, health-related quality of life, perceived stress, the built environment physiological and functional variables such as maximum O2 consumption (VO2max), blood pressure, body composition, handgrip strength, and isokinetic muscle strength. Participants used a triaxial accelerometer for seven days to quantify daily physical activity. We compared continuous variables using the Student's t-test and categorical variables using the x2 test, between APP users and non-users. After univariate analysis, we included the main variables associated with the use of APP in a multiple logistic regression model. Results: 102 participants (28.3%), unrelated to gender, reported using a smartphone APP for physical activity at the time of assessment. Users of APP were younger and had higher education, lower cardiovascular risk, better socioeconomic status, quality of life, cardiorespiratory function, body composition, greater physical fitness and more moderate to vigorous physical activity in daily life. The multiple logistic regression showed that age, hypertension, VO2max, socioeconomic status, and quality of life were the variables most significantly associated with the use of the APP. Conclusions: Smartphone APPs to monitor physical activity are developed for younger adults with better socioeconomic status, lower cardiovascular risk, higher quality of life, and greater cardiorespiratory fitness. Greater efforts are needed to develop a science-based APP for people who most need this technology, enabling greater potential to prevent undesirable health outcomes in asymptomatic adults.